Consumption of ferulic and p-hydroxybenzoic acids by soybean root tips - Silva,Hélio Cândido da (2000)
Depletion method was used to describe how soybean root consumed ferulic and p-hydroxybenzoic acids in nutrient culture. The results showed that excised cultured soybean roots consumed these allelochemicals very rapidly. At concentrations between 0.1 and 1.0 mM, roots consumed 50% or more of ferulic acid after 6-h depletion. Although consumption started only after 3 h, similar behavior was verified with p-hydroxybenzoic acid.